PROPAEDEUTIC OF PROGRAMMING AND NEW SCHOOL REFORM - STOFFOVA, Veronika; CZAKOOVA, Krisztina (Journal of Technology and Information Education, 2012)
Programming as a subject of teaching at elementary and secondary schools in Slovakia went a long way. The new school reform has reintroduced programming into the subject content of Informatics for both primary, and secondary schools in the State educational program. But at the schools, there are not enough qualified teachers to teach programming. The article describes a way how to solve this problem and also deals with response of some universities to need of augmentation of information and programmer literacy of future teachers and teachers in practice.
Keywords: informatics; programming; teaching of programming; programmer literacy